Topological band gap in intercalated epitaxial graphene - Kim, Minsung; Wang, Cai-Zhuang; Tringides, Michael C.; Hupalo, Myron; Ho, Kai-Ming (Solid state communications, 2023)
The study of functional manipulation of graphene is a critical subject, both for fundamental research and practical applications. In this study, we present that the intercalation of 5d transition metals into epitaxial graphene on SiC is a promising strategy for the realization of topologically nontrivial phases with a finite band gap in graphene. Employing first-principles calculations, grounded in density functional theory, we demonstrate that Re- and Ta-intercalated graphene evolve into two-dimensional topological insulators. These exhibit linear Dirac cones and quadratic bands with topological band gaps, respectively. The emergence of these topological states is attributed to the strong spin–orbit coupling strength of the intercalants. We show that the corresponding topological edge states persist within the finite bulk band gap, aligning with the bulk-boundary correspondence. Furthermore, we explore the spin splitting of the band structure, brought about by the inversion symmetry breaking and the spin–orbit coupling. Our study underscores that the intercalation of graphene is an effective and a feasible approach for manipulating the band gap and the topological nature of graphene. Such intercalated graphene systems hold potential utility for spintronics and low-dimensional quantum device applications. •Topological band gaps appear in the Re-intercalated epitaxial graphene on SiC.•Topological band gaps appear in the Ta-intercalated epitaxial graphene on SiC.•Spin-split valence bands in the Re-intercalated epitaxial graphene on SiC.•Rashba-type spin-split bands in the Ta-intercalated epitaxial graphene on SiC.